Caracterização epidemiológica de brucelose e leptospirose de pequenos ruminantes dos estados do Sergipe, Bahia, Ceará e Paraíba - Silva, Glaucenyra Cecília Pinheiro da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brucellosis and leptospirosis are infectious diseases widely geographically distributed that affect domestic and wild animals, as well humans. Because of this, they have economic importance, for losses arising from reproductive disorders and production loss, and also to the public health due to be a zoonosis. Seen the goat importance to the Northeast region, this study aimed to evaluate the presence of antibodies to Leptospira and antibodies to smooth Brucella in small ruminants in the states of Sergipe, Bahia, Ceará and Paraíba, and to assess the more prevalent sorovars of Leptospira spp and the factors associated with the infection. We obtained 6,431 samples of small ruminants, 931 sheep samples and 817 goat samples from Ceará, 443 sheep samples and 1,215 goat samples from Paraíba, from Sergipe 923 sheep samples and 499 goat samples, and 918 sheep samples and 499 goat samples from Bahia. The leptospirosis serologic diagnosis was made through the microscopic agglutination test. To brucellosis the buffered acidified antigen test was used as a screen test and then confirmed using the fluorescence polarization and the complement fixation tests. Leptospirosis was found widely distributed in the studied area, with frequencies of 27.15% (95% CI 25.62 to 28.69) in sheep and 34.34% (95% CI 32.69 to 35.97) in goats. In the state of Paraíba, the frequency was 28.89% (95% CI: 24.67% -33.11%) in sheep and 34.65% (95% CI: 31.97% -37.33%) in goats. In Sergipe, the prevalence in sheep was 12.89% (95% CI 10.73 to 15.05) and 32.67% (95% CI 28.55 to 36.78) in goats. In Ceará, the prevalence was 29.22% (95% CI 26.29 to 32.13) in sheep and 28.52% (95% CI 25.42 to 31.62) in goats, and in Bahia it was 38.56% (95% CI 35.41 to 41.71) in sheep and 41.90% (95% CI 38.20 to 45.59) in goats. The prevalence in herds in the region was 93.26% (95% CI 89.57 to 96.94) in sheep flocks and 97.16% (95% CI 93.52 to 98.78) in goat herds. All municipalities analyzed ...

A brucelose e a leptospirose são doenças infectocontagiosas de ampla distribuição geográfica que acometem animais domésticos, silvestres e o homem. Devido a isso, possuem importância econômica, por perdas advindas de transtornos reprodutivos e para a saúde pública, devido ao fato de serem zoonoses. Tendo em vista a importância da caprinovinocultura para a região Nordeste, este trabalho teve como objetivo avaliar a presença de aglutininas anti-Leptospira e de reação anti-Brucella lisa em pequenos ruminantes de quatro Estados da região nordeste, bem como avaliar os sorovares de Leptospira spp mais prevalentes e os fatores associados à infecção. Foram obtidas 6.431 amostras de pequenos ruminantes. No Estado do Ceará foram 931 amostras de ovinos e 817 de caprinos, na Paraíba foram 443 ovinos e 1.215 caprinos, em Sergipe foram 923 ovinos e 499 caprinos e na Bahia 918 ovinos e 685 caprinos. O diagnóstico sorológico para leptospirose foi feito por meio do teste de soroaglutinação microscópica, para brucelose foi feito o antígeno acidificado tamponado como teste de triagem, e, como confirmatórios foram realizados os testes de polarização fluorescente e de fixação de complemento. A leptospirose encontra-se amplamente distribuída na região estudada, com frequências de 27,15% (IC95%: 25,62-28,69) em ovinos e 34,34% (IC95%: 32,69-35,97) em caprinos. No Estado da Paraíba, as frequências foram 28,89% (IC95%: 24,67%-33,11%) em ovinos e 34,65% (IC95%: 31,97%-37,33%) em caprinos. Em Sergipe, a prevalência em ovinos foi 12,89% (IC95%: 10,73-15,05), e 32,67% (IC95%: 28,55-36,78) em caprinos. No Ceará, 29,22% (IC95%: 26,29-32,13) em ovinos e 28,52% (IC95%: 25,42-31,62) em caprinos; e na Bahia, 38,56% (IC95%: 35,41-41,71) em ovinos e 41,90% (IC95%: 38,20-45,59) em caprinos. A prevalência em rebanhos na região foi 93,26% (IC95%: 89,57-96,94) em rebanhos ovinos e 97,16% (IC95%: 93,52-98,78) em rebanhos...
Keywords: Ovino; Caprino; Leptospirose em animais; Brucelose; Sorologia veterinaria; Veterinary serology